Perancangan User Experience Sistem Informasi Pelaksanaan Praktik Kerja Lapangan berbasis Website menggunakan Pendekatan Human-Centered Design (Studi Kasus: SMKN 2 Kota Serang) - Richard Hans Octavian; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The development of information technology changes every year, the field of education is one field that has a significant impact on the development of information technology. SMKN 2 Serang City is one of the state SMKs located in Serang City, Banten. Students of SMKN 2 Serang City are required to carry out On The Job Training (OTJ) to meet the curriculum requirements, so that students gain experience as a provision in the world of work later. Problems that occur at this time the implementation of street vendors is still done manually, it makes the implementation of street vendors less effective and efficient. To overcome the problems experienced, it takes a web-based information system development to be a solution in solving these problems. In building a website-based information system there is a component called User Experience. One of the methods in designing and developing User experience is to use the Human Centered Design (HCD) approach. This system will be developed by having several features in the form of discussion room pages, search features in discussion rooms, filters in discussion rooms, registration of street vendors, daily attendance logbook, and reporting of street vendors. To get a good User Experience and in accordance with the needs of users, testing of the system is treated, the method used to evaluate the User Experience of a system is one of them using Usability Testing. Based on the results of testing the features contained in the system, the results of testing on 3 aspects of testing are effectiveness, efficiency, and satisfaction.